2023
DOI: 10.1039/d3ee00293d
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of unstable residual lead iodide near the buried interface for the stability improvement of perovskite solar cells

Abstract: In perovskite solar cells, the formation of residual/excess lead iodide (PbI2) in the perovskite film is detrimental to device stability. However, the understanding of the effect of residual/excess PbI2 and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(31 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Moreover, the presence of superfluous PbI 2 distributed at the buried interface and the mismatch of interfacial energy levels further hinder charge transfer and cause V oc loss. [9,10] With this motivation, cumulative efforts (such as morphology modulation of PbI 2 film and crystal-assisted growth) have been devoted to facilitating the conversion of PbI 2 to perovskite, which is imperative to inspire the full potential of PVSCs. [11,12] Previous reports also have revealed that the presence of PbI 2 is considered to be crucial for obtaining excellent photovoltaic properties, deriving from the formation of type-I energy band alignment between PbI 2 and perovskite grain boundaries (GBs).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the presence of superfluous PbI 2 distributed at the buried interface and the mismatch of interfacial energy levels further hinder charge transfer and cause V oc loss. [9,10] With this motivation, cumulative efforts (such as morphology modulation of PbI 2 film and crystal-assisted growth) have been devoted to facilitating the conversion of PbI 2 to perovskite, which is imperative to inspire the full potential of PVSCs. [11,12] Previous reports also have revealed that the presence of PbI 2 is considered to be crucial for obtaining excellent photovoltaic properties, deriving from the formation of type-I energy band alignment between PbI 2 and perovskite grain boundaries (GBs).…”
Section: Introductionmentioning
confidence: 99%
“…18 Furthermore, though using excess PbI 2 in the precursor solution is beneficial to obtaining high device performance, 14 the formation of PbI 2 in the perovskite film is detrimental to device stability. 18,19 To improve the wettability of the substrate for fabricating perovskite films and modulating the perovskite crystallization, various modification strategies of PTAA films and novel hole transport materials have been explored. 20 For example, it is common to use DMF solvent to rinse PTAA films before fabricating perovskite films, which can improve surface wettability to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…18 Furthermore, though using excess PbI 2 in the precursor solution is beneficial to obtaining high device performance, 14 the formation of PbI 2 in the perovskite film is detrimental to device stability. 18,19…”
Section: Introductionmentioning
confidence: 99%
“…2−4 In addition, inhomogeneity of polycrystalline perovskite films due to imperfect stoichiometric ratios, nonequilibrium reactions, and partial evaporation of the organic components also deteriorates the long-term stability of PSCs. 5 For instance, state-of-the-art PSCs have typically utilized excess lead iodide (PbI 2 ) (5−10 mol %) in the precursor solution to prepare polycrystalline perovskite films. 6,7 This is due to the fact that a slight excess of PbI 2 at the perovskite grain boundaries (GBs) and surfaces has some benefits for high efficiency PSCs, including defect passivation, reduction of halide vacancy concentration, and enhancement of carrier lifetime.…”
mentioning
confidence: 99%
“…Nevertheless, the long-term stability of PSCs remains a major barrier to their commercialization. The degradation of PSCs is mainly attributed to the hybrid ionic nature of perovskite materials, which is intrinsically unstable in the presence of moisture, oxygen, heat and light. In addition, inhomogeneity of polycrystalline perovskite films due to imperfect stoichiometric ratios, nonequilibrium reactions, and partial evaporation of the organic components also deteriorates the long-term stability of PSCs . For instance, state-of-the-art PSCs have typically utilized excess lead iodide (PbI 2 ) (5–10 mol %) in the precursor solution to prepare polycrystalline perovskite films. , This is due to the fact that a slight excess of PbI 2 at the perovskite grain boundaries (GBs) and surfaces has some benefits for high efficiency PSCs, including defect passivation, reduction of halide vacancy concentration, and enhancement of carrier lifetime. However, excess PbI 2 can be a double-edged sword for PSCs. , Numerous publications have reported that excess PbI 2 readily decomposes to gaseous I 2 and metallic Pb 0 under light and thermal stress, acting as catalytic sites to trigger perovskite decomposition. It is therefore necessary to manage the unstable PbI 2 in perovskite films to achieve an efficient and stable PSC.…”
mentioning
confidence: 99%